Advances in α-Amylase Technology: Production, Characterization, Engineering, and Functional Applications in Industrial and Biomedical Systems - Rahma Noer Fauziah; Anti Zahrotul Abror; Naela Salma Khasani; Anggie Dhea Aprilia (LAVOISIER: Chemistry Education Journal, 2026)
Abstract α-Amylase is a key industrial enzyme widely utilized in food processing, bioenergy production, and various biotechnological applications due to its ability to hydrolyze starch into simpler sugars. This study aims to comprehensively review recent advancements in α-amylase technology, including its production, characterization, mechanisms of action, engineering strategies, inhibition, and applications in industrial, biomedical, and sustainable systems. The research employed a descriptive-analytical literature review method by analyzing 69 relevant scientific publications from reputable databases such as ScienceDirect, SpringerLink, MDPI, and Google Scholar. The findings indicate that microbial-based production, particularly through the utilization of agro-industrial waste, offers a cost-effective and sustainable approach aligned with circular bioeconomy principles. Enzyme characterization reveals that α-amylase exhibits high adaptability to varying temperature and pH conditions, with performance strongly influenced by physicochemical factors and metal ions. Structural analysis highlights the importance of the GH13 domain in determining catalytic efficiency and substrate specificity. Furthermore, advancements in enzyme engineering, including genetic modification, protein engineering, and immobilization techniques, significantly enhance enzyme stability, reusability, and resistance to extreme conditions. The study emphasizes the importance of enzyme inhibition mechanisms, particularly in medical applications such as diabetes management. Overall, α-amylase technology demonstrates significant potential as a versatile and sustainable biocatalyst. Future developments should focus on optimizing enzyme engineering approaches, exploring novel microbial resources, and integrating advanced biotechnological innovations to enhance efficiency and broaden application potential.